A STUDY ON CHARACTERIZATION OF STANNATE NANO STRUCTURES (International Journal of Food and Nutritional Sciences, 2022)
Zinc stannate is a compound made up of two different types of oxides that may be distinguishedfrom one another by their crystalline structures and zinc to stannous element ratios: both Zn2SnO4and ZnSnO3 Binary semiconducting oxides (II-VI and IV-VI oxides), such as ZnO, TiO2, andSnO2, have attracted a lot of attention as zero- and one-dimensional nanostructures.